Trailblazing in Entrepreneurship Creating New Paths for Understanding the Field - Shepherd, Dean A.; Patzelt, Holger (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
In this book, the authors present a challenge for future research to build a stronger, more complete understanding of entrepreneurial phenomena. They argue that this more complete picture of entrepreneurial phenomena will likely come from scholars who undertake at least some trailblazing projects; from scholars who broaden the range of research questions, the potential outcomes of entrepreneurial action, and the selection and combination of research methods; and from researchers who avoid the endless debates about the margins of the field and its sub-fields or about whether one theoretical or philosophical lens is superior to another. This book offers suggestions for future research through a variety of topics including prosocial action, innovation, family business, sustainability and development, and the financial, social, and psychological costs of failure. It promises to make an important contribution to the development of the field and help academics, organizations, and society make useful contributions to the generation of entrepreneurial research.